Вклад духовно-орієнтованого підходу в ресоціалізації наркозалежної особи - Штейн, Н. Г.; Shtein, N. H. (Вісник Національного університету оборони України. - 2013. - Вип. 5(36). - С. 329-334, 2013)
Стаття присвячена проблемі ресоціалізації залежної поведінки. Представлені різноманітні погляди на дану проблематику представників різних психологічних шкіл. Викладено духовно цілісний підхід до психокорекції залежностей.

The article is concerned with the problem of re-socialization of addictive behavior. Because of drugs abuse there are formed specific patterns of behavior and ways of life that lead to fundamental changes in the relationship of man with himself, with the society. There is happened deresocialization of person who loses the skills of social experience, a system of social connections and relationships. During this process people destroys beliefs and lost socially acceptable forms of behavior that are necessary for a normal life in society. Drugs change artificially consciousness of the person who wants to run away or to hide in a world of illusions from external and internal problems instead of solving them. This article provides diverse views on these issues from points of views of different schools of psychology. There was set out a holistic approach to spiritual psychological correction dependencies. Often unmet needs initiate in people strong psychentonia, to reduce and remove it people use some protection mechanisms of self-regulation (drugs as an “erroneous discharge”).

Статья посвящена проблеме ресоциализации зависимого поведения. Представлены многообразные взгляды на данную проблематику представителей различных психологических школ. Изложен духовно целостный подход к психокоррекции зависимостей.
Contribution of spiritual-oriented approach in resocialization of addicted persones
Keywords: адиктивна поведінка; наркоманія; цілісність; духовність; залежна поведінка; наркозалежна особа; ресоціалізація; addictive behavior; addiction; integrity; spirituality; drug addict; resocialization; аддиктивное поведение; наркомания; целостность; духовность; зависимое поведение; наркозависимое лицо; ресоциализация